Earwitnesses: the type of voice lineup affects the proportion of correct identifications and the realism in confidence judgments - Sarwar, Farhan; Allwood, Carl Martin; Zetterholm, Elisabeth (International Journal of Speech, Language and the Law, 2014)
According to Tulving and Thomson (1973) similarity in encoding and recall contexts will facilitate recall. We investigated if similarity between the original voice event and the voice-lineup helps people to identify the target from a voice-lineup and helps improve the realism in participants’ confidence judgments of the identification reports. Participants (N=199) tried to identify a voice heard in a dialogue context that simulated two males 22 and 27 years old planning a burglary. In the Text-lineup condition six male speakers read a text from a book and in the Dialogue-lineup condition the same speakers had a dialogue with another male speaker. Each recording lasted approx. 30 seconds. The Text-lineup condition showed better identification accuracy, lower overconfidence and better calibration compared with the Dialogue-lineup condition. These results deviate from Tulving and Thomson’s encoding specificity principle in memory psychology, maybe because text reading provides more useful voice features compared to dialogues.